Effect of Hormone Replacement Therapy on Risk of Age-related Macular Degeneration Among an Aggregate Health Record Cohort - Charles W. Guo; Alison H. Zhao; David Kaelber; Rishi P. Singh; Katherine E. Talcott (Ophthalmic Surgery, Lasers and Imaging Retina, 2026)
Background and Objective: Estrogen in hormone replacement therapy (HRT) exerts anti-inflammatory effects believed to oppose age-related macular degeneration (AMD) pathogenesis, but whether HRT can be protective against AMD is contested. The aim of the study was to evaluate the association between HRT use and the risk of development and progression of AMD in postmenopausal women. Patients and Methods: This was a retrospective cohort study utilizing ICD-10 codes for HRT usage and rates of AMD development and progression. Results: There was a decreased risk of developing AMD in patients more than 60 years of age at 5 years (RR 0.72, 95% CI: 0.63–0.82) and 8 years (0.68, 0.60–0.76) after HRT initiation. Patients more than 75 years of age also demonstrated a reduced risk of developing AMD after 5 years (0.70, 0.60–0.82) and 8 years (0.64, 0.56–0.74) of HRT use. Patients more than 75 years of age had a reduced risk of progression to exudative AMD at 8 years (0.66, 0.49–0.89) after HRT initiation. Conclusion: HRT may be associated with a decreased risk of developing AMD, with continued effects at more chronic timepoints after HRT initiation.